Linear equality-constrained least-square problems by generalized QR factorization - Cabrera Miranda, Sergio Andrés (2021)
The generalized QR factorization, also known as GQR factorization, is a method that simultaneously transforms two matrices A and B in a triangular form. In this paper, we show the application of GQR factorization in solving linear equality-constrained least square problems; in addition, we explain how to use GQR factorization for solving quaternion least-square problems through the matrix representation of quaternions.